PEMANFAATAN EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI SENYAWA CHEMOSENSOR - , SANTI OKTAFIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The utilization of the extract of red dragon fruit (Hylocereus polyrhizus) peel as a chemosensor compound has been investigated. Isolation of betacyanin pigment compounds from red dragon fruit peel was carried out by maceration method using ethanol 95%. Extract was then identified with various eluents using Thin Layer Chromatography (TLC) and analyzed by spectrophotometer UV-Vis. Chemosensor tests were conducted by observing the color changes occured in betacyanin extract as the affect of pH solution, specific anions, and some other base compounds. Application to detect the deterioration of fish meat was also investigated in this study. The result revealed that betacyanin extract was red viscous liquid. The best eluent used for separation was acetonitrile:trifluoroacetic acid (TFA) (9.9:0.1) indicating the presence of three stains on the TLC plate. Based on the result of UV-Vis spectra, the appearance of betacyanin compounds was identified in the extract with maximum peak at a wavelength of 538 nm. The concentration betacyanin in this extract was obtained at 13.87 Â± 1.07 mg from 100 g peel of red drasgon fruit. The color changes of betacyanin extract showed that its pigmen compound could act as a chemosensor compound for the titration indicator of weak acid-strong base, sensor for cyanide, carbonate, sulfur anion, ammonia and triethylamine as well as a reagent detector for fish meat deterioration. Betacyanin compounds could be used as a cyanide anion sensor with a limit detection of 5000 ppm and saturated carbonate anion. The betacyanin compounds have also been used to make paper indicator for acid-base and anion sensors. The paper indicator was more effective than liquid form for detection of cyanide anion.